Membangun Jiwa Wirausaha dan Literasi Keuangan melalui Rumah Budaya Perpustakaan Bahagia Mendawai - Zailani Arbain; Anwar Azazi; Alfiyyah Misbahussaniyyah; Damia Raudhatusukma; Syifa Putri Damayanti; Nethlyn Vincyarif Guntur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This program aims to foster economic literacy and entrepreneurial spirit from an early age among children in Kampung Wisata Caping, Pontianak. Through a participatory approach, activities were carried out over 13 days, involving children in the creation of e-books, creative workshops, and practical trading exercises. The results demonstrate increased enthusiasm for learning, awareness of local potential, and the optimization of the library as a culturally-based educational space. This program is expected to serve as the first step toward sustainable empowerment for children.